Editorial - Ratnalikar, N. V. (Journal of Engineering Education Transformations, 2012)
Today, we are having 88 Technical/Technological Universities, of which 34 are State Universities, 32 Deemed to be Universities and 22 Private Universities. A few of these are confined only to one or two disciplines like Management and Information technology. The First Technological University established in India, was in 1972 at Hyderabad (A.P.) i.e. Jawaharlal Nehru Technological University. Thus, the technological universities in India have been functioning for nearly last 2 decades.